Sikap Dan Pemilihan Bahasa Etnik Iban Di Kampung Mentu, Simunjan - Patrose, Abell Musi (Universiti Malaysia Sarawak, (UNIMAS), 2022)
In general, most Malaysians can speak more than one language and are given the option to choose the appropriate language with the addressee, topic, and location. The study aims to explore the languages used by Iban in Kampung Mentu, Sarawak, in five selected domains: family, friendship, occupation, trade and transaction, and religion. This domain was derived from Fishman Domain-Theory (1972). The study also aims to analyze the attitudes of Iban toward language usage. Questionnaires and interview methods were used in the study to obtain the data. One hundred respondents were chosen to participate in the study, and fifteen were interviewed. The questionnaire link direct to Google Form was shared with the respondents. Meanwhile, fifteen respondents were interviewed using the face-to-face method. The finding showed that the Iban language attitudes were closely related to their backgrounds, language use in social environments, and language abilities. The finding indicated that Iban in Kampung Mentu prioritizes their mother tongue within the family, friendship and religion domains. The attitudes towards the usage of Malay and Iban were positive. However, attitudes towards the usage of English were negative. Respondents also perceived Iban and Malay as prestigious compared to other languages. Factors such as lack of eloquence, interest and motivation led to the lack of use of English in the domains studied. The findings indicated that the Iban language attitudes were closely related to their backgrounds, language use in social environments, and language abilities.